2021
DOI: 10.29228/johse.9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Gene Polymorphisms of Vaspin, Visfatin and Chemerin in Diabetic Obese and Non-Diabetic Obese Patients.

Abstract: Diabetes mellitus and obesity are very similar in terms of pathogenesis and pathophysiology. Most obese patients have adipose tissue dysfunction caused by genetic and environmental factors. Adipose tissue is the source of adipokines secreted from adipocytes. Vaspin (visceral adşpose tissue-derived serine protease inhibitor), Visfatin (pre-B cell enhancing factor) and Chemerin are adipokines discovered in recent years. The study consists of 43 non-diabetic obese and 51 diabetic obese individuals. The PCR-RFLP m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Increased accumulation of fatty acid causes adipocyte hypertrophy and impaired bloodstream by triggering the production of proinflammatory cytokines, particularly via the nuclear factor kappa B (NF-κB) signaling pathway. As well as enlargement of the volume of infiltrated macrophages causes synthesis of pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), adiponectin, visfatin, interleukin-1β (IL-1β), and interleukin-6 (IL-6), in adipocytes that are secreted from infiltrated macrophages that lead to the process described as low-grade chronic inflammation (7,17,18). Low-level chronic inflammation in the long-term may turn into chronic systemic inflammation and lead to the occurrence and advancement of metabolism-related disorders, such as IR, hyperlipidemias, hypercholesterolemia, T2DM, cardiovascular diseases, and atherosclerosis (10)(11)(12).…”
Section: Inflammation In Adipose Tissuementioning
confidence: 99%
“…Increased accumulation of fatty acid causes adipocyte hypertrophy and impaired bloodstream by triggering the production of proinflammatory cytokines, particularly via the nuclear factor kappa B (NF-κB) signaling pathway. As well as enlargement of the volume of infiltrated macrophages causes synthesis of pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), adiponectin, visfatin, interleukin-1β (IL-1β), and interleukin-6 (IL-6), in adipocytes that are secreted from infiltrated macrophages that lead to the process described as low-grade chronic inflammation (7,17,18). Low-level chronic inflammation in the long-term may turn into chronic systemic inflammation and lead to the occurrence and advancement of metabolism-related disorders, such as IR, hyperlipidemias, hypercholesterolemia, T2DM, cardiovascular diseases, and atherosclerosis (10)(11)(12).…”
Section: Inflammation In Adipose Tissuementioning
confidence: 99%
“…Diabetes is a metabolic disease that is characterized by elevated blood glucose levels because of impaired insulin secretion and/or activity in cells in the Langerhans Islets of the pancreas [5]. Studies have shown that the relationship between diabetes and obesity is the main cause of insulin resistance which results from body fat distribution, TNF-α, free fatty acids, and gene defects of the β3-adrenergic receptor in the body [6,7].…”
Section: Introductionmentioning
confidence: 99%